Analisis Pengaruh Sudut Penyalaan TRIAC terhadap Pengaturan Kecepatan Motor Induksi Satu Fasa Menggunakan Cycloconverter - Herawati, Afriyastuti; Saputra, Muhammad Alvin; Anggraini, Ika Novia (UNIB Press, 2021)
ABSTRACTA single-phase induction motor is one type of electric motor that is most widely used in everyday’s life, especially for running small loads. The application of this single phase induction motor is not only in households but also in shops, shopping centers, and industry. In its operation, single-phase induction motors can be operated with constant speed and variable speed. The operation of a single-phase induction motor at a constant speed can be done by inputting the nominal voltage and frequency of the motor. Meanwhile, the operation of a single-phase induction motor with varying speeds can be done by adjusting the input frequency of the motor. In this study, an induction motor speed control was carried out using a cycloconverter to regulate the speed of a single-phase induction motor by changing the input frequency of the motor into three variations, namely f / 1, f / 2 and f / 3 at the base frequency of 50 Hz. The cycloconverter switching was designed using TRIAC and then a study was carried out on the effect of the TRIAC’s firing angle on the speed, voltage and output power of the motor by varying firing angles by 0?, 30?, 45?, 60? and 90?. The result show, it is found that increasing the firing angle, the motor output voltage decrease, the motor output power also decrease, except at the angle of 60 ? rises then at the angle of 90 decrease again, while the motor speed increases at the same frequency. Keyword: cycloconverter, firing angle, TRIAC.